Trends in induced abortion among Nordic women aged 40-44 years - Sydsjö Adam; Josefsson Ann; Bladh Marie; Sydsjö Gunilla (BMC, 2011)
Abstract Objectives Women aged 40-44 years in 2005 ought to have been subjected to much more influence on attitudes and knowledge on contraceptive methods during their fertile period than women who were in the same age span in 1975 when the abortion laws were introduced. Material From official statistics, the rates of induced abortion and birth rates in women aged 40-44 years were collected for Sweden, Denmark, Norway and Finland for each five-year during the period 1975-2005. Results With the exception of Sweden all other studied Scandinavian countries have lowered their abortion rates since 1975 (p < 0.001) and reduced the proportion of induced abortions in relation to birth rate (p < 0.001). In 2005 these countries also had lower rates of induced abortion than Sweden in the age group 40-44 years (p < 0.001). Conclusion There is a significant change in rates of induced abortion in women aged 40-44 years in Finland, Norway, Denmark, and at status quo in Sweden. 40-44 years in Finland, Norway, Denmark, and at status quo in Sweden. This indicates that family planning programs works well in the Nordic countries. The differences found may be assumed to possible diverging focus on attitudes or ethical considerations.